The Influence of Entrepreneurship Education and Family Background on Students’ Entrepreneurial Interest in Nutritious Traditional Food Start Ups in Indonesia - Hidayat, Hendra; ., Yuliana (International Journal of Engineering and Technology, 2018)
The entrepreneurial interest of students in higher education tends to be low,albeit the introduction of entrepreneurial education at colleges and universities. There is no exception of lack of interest in entrepreneurship at traditional food businesses where these businesses in Indonesia have an unlimited market share, higher profit, lower riskof loss, and continuous innovation. Entrepreneurial education is not the only determinant asthe students' environment, especially their family background also has an important role in influencing and building student entrepreneur interest. Hence,this study assesses the influence of entrepreneurship education and family background towards the interest of entrepreneurs especially in nutritious traditional foods based on a sample of 150 higher educationstudents. Data was collected usingquestionnaire whiledata was analysed usingdescriptive and multiple regression analyses. The results of the studyshow that entrepreneurial education as well as family background positively affect students’ entrepreneurial interest in traditional food. Therefore, entrepreneurship education should become a serious concern in higher education as can be one the students’ starting point in building the interest and spirit of entrepreneurs.